The impact of religion in shaping the political processes and outcomes in Zimbabwe: the case of Zvishavane, 2008-2015 - Chakabveyo, Calvin (Midlands State University, 2017)
The political-theological problem has been a hot air since Ancient Greece philosophy until the modern political philosophers ranging from Weber, Machiavelli, Nieschtze, Marx among others who declared the death of the religion on the public sphere and being buried by modernity and secularism in the private sphere. The philosophers went on to predict the vanishing of religion even in the private sphere at an earlier stage than now. With the religious groups gaining prominence in the public sphere at global, regional and national level in the 20 th century with mordernity and secularism ressurecting it from the private sphere , one wonders where did the great thinkers got it wrong. The bombing of the pentagon tower in Washington DC on Semptember 11 2001 was a spectacular alarm that broadcasted to the world that religion is a powerful surge that is too big to be locked up in a tiny secretive box, the private sphere. Regionally, there is a legacy of champions of pan Africanism like Nkrumah who held high the banner of African Nationalism and preached that the Africans should seek first the political independence and other pertinent issues would follow. One wonders as to whether the African icon was conscious about the imminent menacing of religion in the independent African states which turned the continent into a hotbed of protracted conflicts. Faced with misfiring of the theories and harsh realities due to religion, the study used the premises of the theorist as the point of departure to examine and exhume the concomitances underlying the political and religious relations in Zvishavane. The study took a form of a case study in a bid to excavate the religious phenomenology in shaping the political processes and outcomes in Zvishavane. The research offered the researcher an ample time to interract with the theist groupings in Zvishavane as a drastic measure to decode their religious attitudes, opinions and actions in relation to the political systems in Zimbabwe. The overhaul was that the symbiotic nature of the umblical cord between religion and politics can not be broken as religion pollutes the tools of self government premised on the individual rigts and liberties. The political terrain of Zvishavane since the Dadaya high school strike in 1947 has been the miniature of the national politics.